2017
DOI: 10.18632/oncotarget.18279
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA-SVUGP2 suppresses progression of hepatocellular carcinoma

Abstract: Numerous studies indicate that long noncoding RNAs (lncRNAs) are dysregulated in hepatocellular carcinoma (HCC) and might serve as potential diagnostic biomarkers and therapeutic targets of HCC. Therefore, it is interesting to globally identify the lncRNAs altered in HCC. In our study, we used microarray to profile the levels of lncRNAs and mRNAs in three pairs of HCC and their adjacent noncancerous samples. We found lncRNA-SVUGP2, which is a splice variant of the UGP2 gene, was down-regulated in HCC samples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Given the crucial role of lncRNAs in biology and etiology, further identification of novel lncRNAs underlying NSCLC development is imperative. LncRNA-SVUGP2 is recently found to have a decreased expression in hepatocellular carcinoma samples and can exhibit tumour-suppressive effects in this malignancy [27]. However, the possible impact of lncRNA-SVUGP2 in other cancers including NSCLC is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Given the crucial role of lncRNAs in biology and etiology, further identification of novel lncRNAs underlying NSCLC development is imperative. LncRNA-SVUGP2 is recently found to have a decreased expression in hepatocellular carcinoma samples and can exhibit tumour-suppressive effects in this malignancy [27]. However, the possible impact of lncRNA-SVUGP2 in other cancers including NSCLC is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of lncRNA-SVUGP2 inhibits the proliferation, migration and invasion of HepG2 and Hep3B HCC cells. 33 It is reported that EGOT plays an oncogenic role in gastric cancer and could be used as a diagnostic and prognostic biomarker. 14 In the present study, we observed that EGOT was significantly highly expressed in HCC cells than that in adjacent normal tissues, which may be associated with elevated markers of advanced malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The method of colony formation experiment referred to the previous research . Cells were seeded into a 3.5 cm dishes at a density of 2000 per dish and cultured in an incubator.…”
Section: Methodsmentioning
confidence: 99%